BISNIS PLAN PENGEMBANGAN USAHA “OPTIKAL” DENGAN BASIS E-BISNIS - Saputra, Nadya Cahya; Mangkuto, Imbang Jaya (Journal of Entrepreneurship, Management and Industry (JEMI), 2018)
This business development plan aims to identify, analyze, and design strategies in developing Biooptik business which is optical business. This business plan uses the analysis of the external environment and the internal environment of the company to determine the strategies to be realized covering four aspects of management namely operational, human resources, marketing and finance. This business plan explains how Biooptik will expand its business by implementing one of the e-business applications so that the revenue will be increased. In this business development plan, Biooptik is conducted a business feasibility study with the addition of 30% of company revenue on the projection of financial statements. This business plan shows that business development is profitable and feasible to run.